Modeling and feedback linearization based sliding mode control of diesel engines for waterjet propulsion vessels. (December 2020) - Xu, Zijing; Gao, Shihang; Han, Yuxiao; Yuan, Jingqi
Abstract: Efficient and stable operation of marine diesel engines is crucial both for navigation maneuverability and safety of waterjet propulsion vessels. In this paper, a piecewise linear model and an affine nonlinear model of marine diesel engines are established by applying mechanism analysis techniques. The models are validated with the experimental data collected from a 290 kW (maximum power) diesel engine equipped on a waterjet propulsion vessel. The relative error of engine speed between model simulation and the measurements is found less than 3%. To improve the performance of the speed regulation system of diesel engines, a sliding mode control strategy is developed on the basis of the affine nonlinear model utilizing the equivalent control method. Simulation results are presented to illustrate the effectiveness of the proposed control strategy regarding model mismatch, response speed, disturbance rejection, and engine speed tracking ability. Highlights: Two models for speed regulation of marine diesel engines are developed. Model validation experiments are carried out on an experimental platform. A feedback linearization sliding mode control strategy is developed.